Modified cyclodextrin inclusion compound flame retardant and flame-retardant polylactic acid composite material
By melt blending of the modified cyclodextrin inclusion flame retardant prepared by using Co-MOF and modified cyclodextrin and polylactic acid, the problems of complex and high cost of the existing bio-based flame retardant preparation process are solved, and the efficient flame retardant, heat reduction and smoke suppression effects of polylactic acid composites are achieved.
Patent Information
- Application Number
- CN202311116434.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The existing bio-based flame retardant preparation process is complex, with low yield and high cost. The flame retardant effect needs to be improved, making it difficult to meet the application needs of polylactic acid in the field of high flame retardant requirements.
A multi-component, multi-structure integrated modified cyclodextrin inclusion flame retardant is prepared by using Co-MOF and aromatic silane modified cyclodextrin containing Schiff base structure, and is melt blended with polylactic acid to prepare flame retardant polylactic acid composite material.
The flame retardant properties of flame retardant polylactic acid composites are improved, heat reduction, smoke suppression and toxic carbon monoxide generation are suppressed, production costs are reduced, and process is simplified.
Smart Images

Figure BDA0004425324430000091 
Figure BDA0004425324430000101 
Figure BDA0004425324430000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant polylactic acid, and in particular relates to a flame-retardant polylactic acid composite material using a modified cyclodextrin inclusion compound as a flame retardant. Background Art
[0002] Polylactic acid (PLA) is a thermoplastic linear aliphatic biodegradable material with good biodegradability, which is conducive to alleviating the increasingly serious energy crisis and environmental pollution problems in the current society. It has many advantages such as abundant raw materials, controllable degradation rate, excellent biocompatibility, good processing performance and mechanical properties, and is widely used in biomedicine, home textiles and clothing, packaging materials and other fields. However, PLA still has the problem of easy combustion and serious dripping when burning, which limits its application and development in the fields of electronics, electrical appliances, automobiles and other fields with high flame retardancy requirements. Therefore, it is necessary to continue to develop flame retardant technology for PLA.
[0003] In the research of flame retardant polylactic acid, adding flame retardant can quickly achieve flame retardancy of PLA. Since PLA is a bio-based degradable polymer, in the application field considering its bio-based properties, adding bio-based flame retardant is preferred in improving the flame retardant properties of PLA.
[0004] Bio-based flame retardant is a flame retardant additive made from biomass, which is environmentally friendly, green, less smoke, low toxicity and biodegradable. In recent years, a large number of studies have used different bio-based materials as reaction substrates to prepare high-efficiency, environmentally friendly and low-carbon bio-based flame retardants, among which organic PN bio-based flame retardants are obtained by reacting bio-based materials such as phytic acid, chitosan, cardanol and lignin.
[0005] However, there are still many problems with various bio-based flame retardants. PA is mainly extracted from rice bran and wheat bran, with a high water content and a boiling point close to that of water, making it difficult to obtain a relatively pure product. Therefore, the purification process is difficult, the production cost is high, and it is difficult to achieve application in the industrial field. The flame retardant effect of chitosan alone is weak, and chitosan needs to be modified to prepare a flame retardant, such as adding DOPO and other phosphorus-containing flame retardants for reaction. However, the flame retardant obtained has problems such as high cost, complex modification method, and impact on fabric durability, and further development and optimization of performance is still needed.
[0006] At present, there are still many problems in the preparation of bio-based flame retardants, such as complex preparation process, low yield, high cost, and flame retardant effect needs to be improved. Therefore, further research and development of bio-based flame retardants is needed to simplify the process, reduce costs, and improve the flame retardant properties, mechanical properties and machinability of flame-retardant polylactic acid. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a flame-retardant polylactic acid composite material based on Schiff base, cyclodextrin and Co-MOF, and a multi-component, multi-structure integrated modified cyclodextrin inclusion compound flame retardant is prepared by using Co-MOF and aromatic silane modified cyclodextrin containing Schiff base structure, and a flame-retardant polylactic acid composite material is prepared by using the flame retardant. Its flame retardant performance, heat reduction and smoke suppression are all improved, and it can effectively inhibit the generation of toxic carbon monoxide.
[0008] The object of the present invention is to provide a modified cyclodextrin inclusion compound flame retardant, which is an inclusion compound of Co-MOF (cobalt organic framework material) modified cyclodextrin and siloxane phenyl Schiff base. It is prepared by using siloxane phenyl Schiff base and Co-MOF modified cyclodextrin.
[0009] The object of the present invention is to provide a method for preparing the modified cyclodextrin inclusion compound flame retardant. The method specifically comprises the following steps:
[0010] Step 1. Prepare siloxane phenyl Schiff base;
[0011] Step 2. Prepare Co-MOF modified cyclodextrin;
[0012] Step 3. Add the siloxane phenyl Schiff base to the Co-MOF modified cyclodextrin solution, stir and react, and obtain a modified cyclodextrin inclusion compound flame retardant.
[0013] Another object of the present invention is to provide the use of the modified cyclodextrin inclusion compound flame retardant for flame retardant polylactic acid and preparation of flame retardant polylactic acid composite materials.
[0014] Another object of the present invention is to provide a flame retardant polylactic acid composite material, which is prepared by melt blending polylactic acid and a modified cyclodextrin inclusion compound flame retardant.
[0015] The present invention also aims to provide a method for preparing the flame-retardant polylactic acid composite material, wherein the flame-retardant polylactic acid composite material is prepared by melt blending polylactic acid and a modified cyclodextrin inclusion compound flame retardant.
[0016] The melt blending temperature is 150-205°C, preferably 160-195°C, and more preferably 170-185°C.
[0017] The modified cyclodextrin inclusion compound flame retardant and flame retardant polylactic acid composite material and the preparation method thereof provided by the present invention have the following beneficial effects:
[0018] (1) In the present invention, siloxane containing primary amine groups and phenyl aldehyde compounds are used to prepare siloxane phenyl Schiff base, and the siloxane phenyl Schiff base and Co-MOF modified cyclodextrin are used to prepare a flame retardant. The Schiff base structure can cross-link into carbon during the combustion process of polylactic acid, thereby improving the flame retardant properties of flame-retardant polylactic acid composite materials.
[0019] (2) In the present invention, 2-methylimidazole and cobalt salt are used to form Co-MOF on the outside of cyclodextrin to modify cyclodextrin, which can play a catalytic role. During the combustion process, the cross-linking process of siloxane phenyl Schiff base and cyclodextrin into carbon is accelerated to improve the flame retardancy of cyclodextrin.
[0020] (3) In the present invention, the modified cyclodextrin inclusion compound flame retardant obtained by the reaction of siloxane phenyl Schiff base and Co-MOF modified cyclodextrin plays a role in the molecular scale to the greatest extent, and the charring rate after its own combustion is greatly improved, which is beneficial to improving the flame retardancy of polylactic acid.
[0021] (4) The modified cyclodextrin inclusion compound flame retardant prepared by the present invention uses less amount of flame retardant, and the obtained flame retardant polylactic acid composite material has a 11% decrease in heat release peak (pHRR) value compared with polylactic acid, a 16.4% decrease in total heat release (THR), a smoke generation rate (SPR) that is almost reduced to 0, and a carbon monoxide production (COY) that is reduced from 0.4 to 0.02, a decrease of up to 95%. Therefore, the modified cyclodextrin inclusion compound flame retardant has the effects of flame retardancy, heat reduction, smoke suppression, and inhibition of toxic carbon monoxide generation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The SEM image of the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 of the present invention is shown;
[0023] Figure 2 The EDS spectrum of the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 of the present invention is shown;
[0024] Figure 3 The XPS full spectrum of the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 of the present invention is shown;
[0025] Figure 4 The Co 2p high-resolution XPS spectrum of the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 of the present invention is shown;
[0026] Figure 5 The thermogravimetric analysis curves of the raw material cyclodextrin of the present invention and the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 are shown;
[0027] Figure 6The infrared spectra of the cyclodextrin of the present invention, the triethoxysilylpropyl (o-hydroxyphenyl) Schiff base prepared in Example 1, the Schiff base cyclodextrin inclusion compound, and the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 are shown;
[0028] Figure 7 The infrared spectra of degradation products of polylactic acid (PLA) of the present invention and flame-retardant polylactic acid composite material II prepared in Example 2 are shown;
[0029] Figure 8 The carbon monoxide (2184 cm -1 ) The release amount variation curve with the increase of decomposition temperature (burning time);
[0030] Fig. 9 The hydrocarbon substances (2741cm -1 ) The release amount change curve with the increase of decomposition temperature (burning time). DETAILED DESCRIPTION
[0031] The present invention is described in detail below through specific implementation modes, and the characteristics and advantages of the present invention will become clearer and more specific with these descriptions.
[0032] The present invention provides a modified cyclodextrin inclusion compound flame retardant, which is an inclusion compound of Co-MOF (cobalt organic framework material) modified cyclodextrin and siloxane phenyl Schiff base, and is prepared by using siloxane phenyl Schiff base and Co-MOF modified cyclodextrin.
[0033] The invention also provides a method for preparing the modified cyclodextrin inclusion compound flame retardant.
[0034] The method specifically comprises the following steps:
[0035] Step 1. Prepare siloxane phenyl Schiff base.
[0036] Adding siloxane containing primary amine groups to a phenylaldehyde compound solution, reflux reaction under a protective atmosphere, and removing the solvent to obtain a siloxane phenyl Schiff base. The protective atmosphere is preferably nitrogen and / or argon, more preferably nitrogen.
[0037] The siloxane containing a primary amine group is selected from aminoalkyl alkoxysilane, wherein the aminoalkyl group is selected from aminoalkyl groups having a carbon number of 2-6, preferably aminoalkyl groups having a carbon number of 2-4, such as aminopropyl; and the alkoxy group is selected from alkoxy groups having a carbon number of 2-5, preferably alkoxy groups having a carbon number of 2-3, such as ethoxy, preferably 3-aminopropyltriethoxysilane.
[0038] The phenylaldehyde compound is selected from one or more of benzaldehyde compounds, phenylacetaldehyde compounds and phenylpropionaldehyde compounds, preferably one or more of benzaldehyde compounds and phenylacetaldehyde compounds, more preferably one or more of hydroxyl-containing benzaldehyde compounds, such as salicylaldehyde.
[0039] The molar ratio of the siloxane containing primary amine groups to the phenyl aldehyde compound is 1:(0.6-1.9), preferably 1:(0.8-1.6), and more preferably 1:(1-1.3).
[0040] The solvent is selected from one or more alcohol solvents, preferably one or more of ethanol, propanol and isopropanol, more preferably ethanol.
[0041] The molar volume ratio of the phenylaldehyde compound to the solvent is 0.1 mol:(60-140) mL, preferably 0.1 mol:(70-130) mL, and more preferably 0.1 mol:(80-120) mL.
[0042] Step 2. Prepare Co-MOF modified cyclodextrin.
[0043] The cobalt salt solution is added to the cyclodextrin solution, and then the 2-methylimidazole solution is added, and the mixture is stirred for reaction to obtain the Co-MOF modified cyclodextrin.
[0044] The cobalt salt is selected from alcohol-soluble cobalt salts, preferably selected from one or more of cobalt nitrate, cobalt acetate, cobalt chloride and cobalt sulfate.
[0045] The molar mass ratio of the cobalt salt to cyclodextrin is 7 mmol:(1-7) g, preferably 7 mmol:(2-6) g, and more preferably 7 mmol:(3-5) g.
[0046] The molar ratio of the cobalt salt to 2-methylimidazole is 0.007:(0.010-0.060), preferably 0.007:(0.020-0.050), and more preferably 0.007:(0.025-0.040).
[0047] The solvent of the cobalt salt solution, cyclodextrin solution and 2-methylimidazole solution is selected from one or more alcohol solvents, preferably one or more of methanol, ethanol and isopropanol, more preferably methanol.
[0048] The reaction temperature is 25-80°C, preferably 25-40°C; the reaction time is 8-16 hours, preferably 10-14 hours.
[0049] After the reaction is completed, the product is separated by centrifugation and dried to obtain modified cyclodextrin.
[0050] Step 3. Add the siloxane phenyl Schiff base to the Co-MOF modified cyclodextrin solution, stir and react, and obtain a modified cyclodextrin inclusion compound flame retardant.
[0051] The mass ratio of the siloxane phenyl Schiff base to the Co-MOF modified cyclodextrin is 1:(1-6), preferably 1:(1.5-5), and more preferably 1:(2-4).
[0052] In the modified cyclodextrin solution, the solvent is selected from one or more of water and alcohol solvents, preferably one or more of water, methanol, ethanol and isopropanol, and more preferably a mixed solvent of water and methanol.
[0053] The reaction temperature is 20-35°C, preferably 25-30°C; the reaction time is 8-16 hours, preferably 10-14 hours.
[0054] The modified cyclodextrin inclusion flame retardant provided in the present invention can make the polymer condensation phase carbonized during the combustion process. The present invention is designed to utilize the hydrophobic cavity structure and the polyhydroxy structure of the outer surface of cyclodextrin, and successfully utilize the coordination of hydroxyl and cobalt salt to grow Co-MOF on the surface of cyclodextrin. And the hydrophobic siloxane phenyl Schiff base is loaded inside the Co-MOF modified cyclodextrin to prepare the inclusion compound. Among them, the main molecule cyclodextrin itself is an excellent carbon source, the siloxane phenyl Schiff base has the effect of self-crosslinking carbonization at high temperature, and the MOF containing cobalt element has the ability to catalyze the cyclodextrin carbon source and Schiff base to further carbonize. The modified cyclodextrin inclusion flame retardant in the present invention is different from the simple physical blending of Co-MOF, Schiff base and cyclodextrin. The three-group integrated design can make the three components work together at the molecular scale to the greatest extent. Secondly, the Schiff base inside the cyclodextrin is protected by cyclodextrin to achieve the function of sustained release, and the Schiff base action temperature is adjusted to a suitable temperature to play a role at the appropriate temperature stage of polymer decomposition.
[0055] The modified cyclodextrin inclusion compound flame retardant provided by the invention is used for flame retardation of polylactic acid and preparation of flame retardant polylactic acid composite material.
[0056] The invention provides a flame retardant polylactic acid composite material, which is prepared by melt blending polylactic acid and a modified cyclodextrin inclusion compound flame retardant.
[0057] The modified cyclodextrin inclusion compound flame retardant accounts for 1-9% of the total mass of the polylactic acid and the modified cyclodextrin inclusion compound flame retardant, preferably 3-7%, and more preferably 4-6%.
[0058] The present invention also provides a method for preparing the flame-retardant polylactic acid composite material, wherein the flame-retardant polylactic acid composite material is prepared by melt-blending polylactic acid and a modified cyclodextrin inclusion compound flame retardant.
[0059] The melt blending temperature is 150-205°C, preferably 160-195°C, and more preferably 170-185°C.
[0060] The modified cyclodextrin inclusion compound flame retardant accounts for 1-9% of the total mass of the polylactic acid and the modified cyclodextrin inclusion compound flame retardant, preferably 3-7%, and more preferably 4-6%.
[0061] The modified cyclodextrin inclusion complex flame retardant in the present invention is different from bio-based flame retardants such as phytic acid and lignin. Cyclodextrin has a unique hydrophobic cavity structure and a polyhydroxy structure on the outer surface. The siloxane phenyl Schiff base and Co-MOF multi-components are integrated by utilizing its external and internal spatial structures. Similar flame retardants have not been disclosed in other literature.
[0062] The modified cyclodextrin inclusion compound flame retardant in the present invention can simultaneously exert the synergistic flame retardant effect and slow-release effect of the three components. It is superior to simple physical blending and exerts flame retardant effect at the molecular scale. Therefore, the flame retardant efficiency is high. For example, only the mass fraction is 5% and the limiting oxygen index is 29%, which belongs to the flame retardant material.
[0063] In addition, flame retardancy of polylactic acid is often achieved by phosphorus-containing flame retardants, but phosphorus-containing flame retardants tend to accelerate polymer droplets and the secondary fire hazards they bring. The modified cyclodextrin inclusion compound flame retardant in the present invention uses a phosphorus-free component to achieve efficient flame retardancy of the polymer.
[0064] In the present invention, a modified cyclodextrin inclusion compound flame retardant is prepared by using siloxane phenyl Schiff base and Co-MOF modified cyclodextrin. The preparation process is reliable, the conditions are mild and controllable, the production cost of the flame retardant can be reduced, the carbonization rate is greatly improved during the combustion process, and the performance of the flame retardant is improved. When a low amount of the flame retardant is added to polylactic acid, the limiting oxygen index of the flame-retardant polylactic acid composite material is improved, and the heat release peak (pHRR), total heat release (THR), smoke generation rate (SPR) and carbon monoxide production (COY) are all reduced to varying degrees, thereby achieving the purpose of improving the flame retardant performance of polylactic acid.
[0065] Example
[0066] Example 1
[0067] 0.1 mol of salicylaldehyde was added to a three-necked flask containing 100 ml of anhydrous ethanol, and stirred under reflux (about 85° C.) under a nitrogen atmosphere. 0.1 mol of 3-aminopropyltriethoxysilane was added to the above reaction apparatus, and the reaction was carried out at this temperature for 6 hours. After the reaction was completed and the temperature was lowered to room temperature, the ethanol was removed by rotary evaporation to obtain triethoxysilylpropyl(o-hydroxyphenyl)Schiff base ((E)-2-(((3-(triethoxysilyl)propyl)imino)methyl)phenol).
[0068]
[0069] 4 g of cyclodextrin was placed in 100 mL of methanol and stirred at room temperature to obtain solution A. 2 g (about 0.007 mol) of cobalt nitrate hexahydrate was added to 50 mL of methanol, stirred at room temperature until it was completely dissolved, and then added to solution A. 3.08 g (about 0.038 mol) of 2-methylimidazole was added to 50 mL of methanol and stirred at room temperature to obtain solution B. Solution A was mixed with solution B, stirred at 30°C, 400 rpm for 12 hours, centrifuged, and dried in a forced air drying oven at 80°C to obtain Co-MOF modified cyclodextrin.
[0070] 3g of the above Co-MOF modified cyclodextrin was placed in a mixed solution of 80ml methanol and water (methanol and water volume ratio is 3:2), and stirred to mix. Then 1g of triethoxysilylpropyl (o-hydroxyphenyl) Schiff base was added dropwise into the above solution, ultrasonicated for 10min, and stirred at 30°C for 12 hours. The solid product was washed with ethanol and filtered, and dried at 80°C to obtain a flame retardant (modified cyclodextrin inclusion flame retardant) of Co-MOF modified cyclodextrin inclusion triethoxysilylpropyl (o-hydroxyphenyl) Schiff base.
[0071] Example 2
[0072] Polylactic acid (PLA) (Natureworks, USA, brand 6201D, melt viscosity 1.08g / cc, melting point 160-170°C) and the modified cyclodextrin inclusion compound flame retardant prepared in Example 1 were dried in a DZF-6050 vacuum oven at 80°C for 12 hours. Then they were added to a Haake type internal mixer and a flame retardant polylactic acid composite material was prepared by melt blending. The rotor speed used was 50r / min, the mixing time was 5 minutes, and the mixing temperature was 180-175°C. The dosage ratios of PLA and modified cyclodextrin inclusion compound flame retardant are shown in Table 1, and flame retardant polylactic acid composite material I, flame retardant polylactic acid composite material II, and flame retardant polylactic acid composite material III were prepared.
[0073] Table 1
[0074]
[0075] Experimental example
[0076] Experimental Example 1
[0077] The modified cyclodextrin inclusion compound flame retardant prepared in Example 1 was subjected to scanning electron microscopy (SEM) test and X-ray energy spectrum (EDS) test. The test results are as follows: Figure 1 shown.
[0078] From the SEM images ( Figure 1), the morphology of the modified cyclodextrin inclusion flame retardant can be clearly seen, and the Co-MOF crystals (ZIF-67) grown on the outer surface of cyclodextrin. Its EDS spectrum can scan Si, Co, N elements (such as Figure 2 shown).
[0079] Experimental Example 2
[0080] The modified cyclodextrin inclusion compound flame retardant prepared in Example 1 was analyzed by X-ray photoelectron spectroscopy (XPS). Figure 3 shown.
[0081] The analysis showed that the modified cyclodextrin inclusion flame retardant contained C, O, Co, N, and Si elements, which was consistent with the EDS analysis results, confirming that triethoxysilylpropyl (o-hydroxyphenyl) Schiff base was successfully loaded as a guest molecule in the cyclodextrin cavity. The outer surface of Co-MOF modified cyclodextrin is a polyhydroxy structure with hydrophilicity. The triethoxysilylpropyl (o-hydroxyphenyl) Schiff base with hydrophobic groups is difficult to combine with the hydroxyl structure on the outer surface of Co-MOF modified cyclodextrin. The internal cavity of Co-MOF modified cyclodextrin is a hydrophobic structure. Under ultrasound-assisted conditions, triethoxysilylpropyl (o-hydroxyphenyl) Schiff base can be loaded as a guest molecule into the main body of Co-MOF modified cyclodextrin through adsorption and other effects.
[0082] XPS Co 2p high-resolution spectrum ( Figure 4 ) confirmed that Co existed in a divalent form and coordinated with 2-methylimidazole to form a metal organic framework (MOF) Co 2p high-resolution spectrum. Co 2p3 / 2 and Co 2p1 / 2 peaks appeared at binding energies of 781.2 eV and 796.8 eV, which were the Co of Co-MOF ZIF-67 crystal. 2+ In addition, Co can be observed at binding energies of 786.3 and 803.1 eV. 2+ The typical satellite peak (denoted as "Sat") is consistent with the ZIF-67 reported in the literature (Li, L., Yang, L., Zou, R. et al. Facile and scalable preparation of ZIF-67decorated cotton fibers as recoverable and efficient adsorbents for removal of malachite green. J Leather Sci Eng 3, 28 (2021).).
[0083] Experimental Example 3
[0084] Thermogravimetric analysis was performed on the raw material cyclodextrin and the modified cyclodextrin inclusion compound flame retardant prepared in Example 1. The thermogravimetric curves are as follows: Figure 5 shown.
[0085] Through analysis, it was found that the carbon residue of the modified cyclodextrin inclusion compound flame retardant at 700°C was 24.7%, which was three times the carbon residue of the raw cyclodextrin at 700°C (6.2%), indicating that the modified cyclodextrin inclusion compound flame retardant with the characteristics of a ternary integrated Schiff base in the present invention effectively improved its own carbon-forming ability.
[0086] Experimental Example 4
[0087] Infrared spectroscopy analysis was performed on cyclodextrin, triethoxysilylpropyl (o-hydroxyphenyl) Schiff base, Schiff base cyclodextrin inclusion complex, and modified cyclodextrin inclusion complex flame retardant. The specific infrared spectra are shown in the following figure: Figure 6 shown.
[0088] from Figure 6 It can be seen that the infrared spectrum is located at 1630cm -1 The characteristic peak at 1080 cm corresponds to the C=N structure in triethoxysilylpropyl (o-hydroxyphenyl) Schiff base. -1 represents Si-OC vibration. Located at 578cm -1 The Co-O characteristic peak further confirms that the Co-MOF structure exists in the modified cyclodextrin inclusion compound flame retardant prepared in Example 1.
[0089] Put 3g of cyclodextrin into 80ml of a mixed solution of methanol and water (methanol and water volume ratio is 3:2), and stir to mix. Then add 1g of triethoxysilylpropyl (o-hydroxyphenyl) Schiff base dropwise into the above solution, ultrasonicate for 10min, and stir to react for 12 hours at 30°C. Wash with ethanol and filter to obtain a solid product, which is dried at 80°C to obtain a Schiff base cyclodextrin inclusion complex. The Schiff base cyclodextrin inclusion complex sample can be found in the infrared spectrum at 1630cm -1 The characteristic peak of Schiff base structure appears at the corresponding position.
[0090] Experimental Example 5
[0091] The limiting oxygen index and UL-94 vertical combustion tests were performed on polylactic acid (PLA) and the flame-retardant polylactic acid composite material I, flame-retardant polylactic acid composite material II and flame-retardant polylactic acid composite material III prepared in Example 2, and the test results are shown in Table 2. It can be seen that the LOI of the flame-retardant polylactic acid composite material II can reach 29%, which is a flame-retardant material. The UL-94 can reach the V-2 level, and the ignition time is shortened to varying degrees compared with pure polylactic acid. As the amount of the modified cyclodextrin inclusion compound flame retardant increases, the ignition time is gradually shortened.
[0092] Table 2
[0093]
[0094] Experimental Example 5
[0095] Cone calorimetry tests were performed on polylactic acid (PLA) and the flame retardant polylactic acid composite material II prepared in Example 2, and the test results are shown in Table 3. Relative to PLA, the heat release peak (pHRR) of the flame retardant polylactic acid composite material II decreased by 11%, the total heat release (THR) decreased by 16.4%, the smoke generation rate (SPR) was almost reduced to 0, and the carbon monoxide production (COY) decreased from 0.4 to 0.02, a decrease of up to 95%. It shows that the modified cyclodextrin inclusion compound flame retardant provided by the present invention is applied to polylactic acid to play the effect of flame retardancy, heat reduction, smoke suppression, and inhibition of toxic carbon monoxide generation.
[0096] Table 3
[0097]
[0098] Experimental Example 6
[0099] Polylactic acid (PLA) and the flame-retardant polylactic acid composite material II prepared in Example 2 were thermally degraded in a nitrogen atmosphere from room temperature to 700°C at a heating rate of 10°C / min, and the degradation products were tested by infrared spectroscopy. Figure 7 The infrared spectra of the products of PLA and flame-retardant polylactic acid composite material II at the maximum thermal decomposition rate (PLA spectrum at 35 minutes, flame-retardant polylactic acid composite material II spectrum at 30 minutes). The samples all showed characteristic peaks of water, hydrocarbons, CO, CO2, and carbon-based compounds.
[0100] Similar to the cone calorimetry results, carbon monoxide (2184 cm -1 )( Figure 8 ) and flammable hydrocarbons (2741cm -1 )( Fig. 9 ) production is greatly reduced, which provides a theoretical basis for the heat reduction and flame retardancy of flame retardant polylactic acid composite materials II.
[0101] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A modified cyclodextrin inclusion compound flame retardant, which is an inclusion compound of Co-MOF modified cyclodextrin and siloxane phenyl Schiff base.
2. The modified cyclodextrin inclusion compound flame retardant according to claim 1, characterized in that: It is prepared by using siloxane phenyl Schiff base and Co-MOF modified cyclodextrin.
3. A method for preparing a modified cyclodextrin inclusion compound flame retardant, characterized in that: The method specifically comprises the following steps: Step 1. Prepare siloxane phenyl Schiff base; Step 2. Prepare Co-MOF modified cyclodextrin; Step 3. Add the siloxane phenyl Schiff base into the Co-MOF modified cyclodextrin solution, stir and react, and obtain a modified cyclodextrin inclusion compound flame retardant.
4. The method according to claim 3, characterized in that In step 1, a siloxane containing a primary amino group is added to a phenylaldehyde compound solution, refluxed, and the solvent is removed to obtain a siloxane phenyl Schiff base. The siloxane containing a primary amine group is selected from aminoalkylalkoxysilane, wherein the aminoalkyl group is selected from aminoalkyl groups having a carbon number of 2-6, preferably aminoalkyl groups having a carbon number of 2-4, such as aminopropyl; the alkoxy group is selected from alkoxy groups having a carbon number of 2-5, preferably alkoxy groups having a carbon number of 2-3, such as ethoxy, preferably 3-aminopropyltriethoxysilane, The phenylaldehyde compound is selected from one or more of benzaldehyde compounds, phenylacetaldehyde compounds and phenylpropionaldehyde compounds, preferably one or more of benzaldehyde compounds and phenylacetaldehyde compounds, more preferably one or more of hydroxyl-containing benzaldehyde compounds, such as salicylaldehyde.
5. The method according to claim 3, characterized in that: In step 1, the molar ratio of the siloxane containing primary amine groups to the phenylaldehyde compound is 1:(0.6-1.9), preferably 1:(0.8-1.6), and more preferably 1:(1-1.3).
6. The method according to claim 3, characterized in that In step 1, the solvent is selected from one or more alcohol solvents, preferably one or more of ethanol, propanol and isopropanol. The molar volume ratio of the phenylaldehyde compound to the solvent is 0.1 mol:(60-140) mL, preferably 0.1 mol:(70-130) mL, and more preferably 0.1 mol:(80-120) mL.
7. The method according to claim 3, characterized in that In step 2, the cobalt salt solution is added to the cyclodextrin solution, and then the 2-methylimidazole solution is added and stirred to react to obtain Co-MOF modified cyclodextrin. The cobalt salt is selected from alcohol-soluble cobalt salts, preferably selected from one or more of cobalt nitrate, cobalt acetate, cobalt chloride and cobalt sulfate. The molar mass ratio of the cobalt salt to the cyclodextrin is 7 mmol:(1-7) g, preferably 7 mmol:(2-6) g, more preferably 7 mmol:(3-5) g, The molar ratio of the cobalt salt to 2-methylimidazole is 0.007:(0.010-0.060), preferably 0.007:(0.020-0.050), and more preferably 0.007:(0.025-0.040).
8. The method according to claim 3, characterized in that In step 3, the mass ratio of the siloxane phenyl Schiff base to the Co-MOF modified cyclodextrin is 1:(1-6), preferably 1:(1.5-5), and more preferably 1:(2-4).
9. A flame retardant polylactic acid composite material, characterized in that: It is prepared by melt blending polylactic acid with the modified cyclodextrin inclusion compound flame retardant according to claim 1 or 2 or the modified cyclodextrin inclusion compound flame retardant prepared according to one of claims 3 to 8, The modified cyclodextrin inclusion compound flame retardant accounts for 1-9% of the total mass of the polylactic acid and the modified cyclodextrin inclusion compound flame retardant, preferably 3-7%, and more preferably 4-6%.
10. A method for preparing the flame-retardant polylactic acid composite material according to claim 9, characterized in that: The invention is prepared by melt-blending polylactic acid with a modified cyclodextrin inclusion compound flame retardant. The melt blending temperature is 150-205°C, preferably 160-195°C, and more preferably 170-185°C.